Pengaruh Kualitas Produk dan Citra Merek terhadap Keputusan Pembelian Produk Mie Gaga pada Pengguna Instagram JABODETABEK - Viki Sulistia; Refany Novia Siboro (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Changes in people's lifestyles in the era of globalization demand that everything becomes fast and practical, including in fulfilling food needs. This has led to significant growth in the fast food industry, including instant noodle products. This study aims to analyze the influence of brand image and product quality on the purchasing decisions of Mie Gaga products among Instagram users in the Jabodetabek area. This research is motivated by the differing results of previous studies regarding the influence of brand image and product quality on purchasing decisions. The method used is quantitative with a survey approach, utilizing online questionnaires distributed via Google Forms. The sample in this study consisted of 80 respondents, determined based on the formula by Hair et al. (2010). Data analysis techniques include Classical Assumption Tests such as Autocorrelation Test, Multicollinearity Test, Normality Test, and Heteroscedasticity Test, as well as Multiple Linear Regression analysis using SPSS version 22. The results of this study are expected to provide a deeper understanding of the factors influencing purchasing decisions of Mie Gaga products, particularly through the Instagram social media platform. Keywords: , Brand ImGE, Purchasing Decisions